2013
DOI: 10.1158/0008-5472.can-13-0080
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Decreases Glucose Oxidation and Increases the Dependency of Prostate Cancer Cells on Reductive Glutamine Metabolism

Abstract: Metformin inhibits cancer cell proliferation and epidemiology studies suggest an association with increased survival in cancer patients taking metformin, however, the mechanism by which metformin improves cancer outcomes remains controversial. To explore how metformin might directly affect cancer cells, we analyzed how metformin altered the metabolism of prostate cancer cells and tumors. We found that metformin decreased glucose oxidation and increased dependency on reductive glutamine metabolism in both cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
190
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(213 citation statements)
references
References 46 publications
17
190
3
3
Order By: Relevance
“…Consistently metformin, an inhibitor of mitochondrial complex I, provokes a decrease of proliferation with a subsequent activation of reductive glutamine metabolism in vitro and in a TRAMP mouse model [159,170]. Moreover, a combinatorial therapy of metformin and an inhibitor of glutamine metabolism might be promising for therapeutics, since PC-3 and DU-145 cell lines are reportedly glutamine addicted [171,172], and respiration and fatty acid biosynthesis could thus be inhibited simultaneously [170].…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 97%
“…Consistently metformin, an inhibitor of mitochondrial complex I, provokes a decrease of proliferation with a subsequent activation of reductive glutamine metabolism in vitro and in a TRAMP mouse model [159,170]. Moreover, a combinatorial therapy of metformin and an inhibitor of glutamine metabolism might be promising for therapeutics, since PC-3 and DU-145 cell lines are reportedly glutamine addicted [171,172], and respiration and fatty acid biosynthesis could thus be inhibited simultaneously [170].…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 97%
“…In addition, [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glutamine labeling provides a more accurate measurement of reductive carboxylation of α-ketoglutarate to citrate, since this carbon is lost as carbon dioxide by α-ketodehydrogenase in the oxidative pathway but is retained if reductive carboxylation is active (27). By culturing stable C4-2 cells supplemented with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glutamine as tracers, we identified the enrichment of citrate m+1 in control cells expressing nontargeting shRNA (shNT), whereas ablation of SRC-2 showed a significant and robust decrease in the percentage of citrate m+1 ( Figure 2B). In addition, SRC-2 knockdown also decreased the levels of α-ketoglutarate m+1 ( Figure 2C), confirming that SRC-2 regulates the flow of carbon from glutamine to promote the reductive carboxylation of α-ketoglutarate in prostate cancer cells.…”
Section: Src-2 Regulates Lipogenesis By Reductive Glutamine Metabolismentioning
confidence: 99%
“…As AMPK negatively regulates glucose consumption in cancer cells (Faubert et al 2013), the effect of metformin on AMPK phosphorylation was associated with a significant doseand time-dependent reduction in FDG uptake. In a mouse model of prostate cancer, it has been shown that the decreased glucose oxidation exerted by metformin induces the dependency on reductive glutamine metabolism, which is an important source of cellular energy (Fendt et al 2013). Glutamine is a substrate in the production of biochemical intermediates for the tricarboxylic acid (TCA) cycle.…”
Section: Metformin's Effect On Glucose Uptake: Fluoro-deoxy-glucose Imentioning
confidence: 99%